THE EFFECT OF SERVICE QUALITY ON CONSUMER SATISFACTION AT TEH POCI PERUMNAS 1, BEKASI - Ratih Fitri Yatun; Sri Rahayu Puspita Sari (International Journal Management and Economic, 2026)
The purpose of this study was to determine the partial and simultaneous influence of service quality on customer satisfaction at Teh Poci Perumnas 1, Bekasi. The data used were primary data, using a questionnaire distributed to 100 consumers of Teh Poci Perumnas 1, Bekasi. The sampling technique used was purposive sampling. The analytical tools used were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, determinant test, f-test, and t-test. The results showed that the variables Reliability, Assurance, and Physical Evidence partially influenced Customer Satisfaction at Teh Poci Perumnas 1, Bekasi. Meanwhile, the variables Responsiveness and Empathy did not have a partial effect on Customer Satisfaction at Teh Poci Perumnas 1, Bekasi. The variables Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence jointly influenced Customer Satisfaction at Teh Poci Perumnas 1, Bekasi.